Aplikasi Dosen Wali Universitas Madura Berbasis Android - Handi Ghoffar; Sholeh Rachmatullah (Prosiding SISFOTEK, 2021)
The development of technology now greatly affects various aspects of life, including in the world of education. In the highest education, the University should have implemented technology to make it easier for Lecturer Guardians and Student Guardians to monitor student academic and administrative developments such as viewing Study Results Cards (KHS), Study Plan Cards (KRS), transcripts and bills and payments. So far, only students can see academic and administrative developments of students, so it is difficult for student guardians to monitor the development of their sons and daughters because there is no access for student guardians to see academic and administrative developments of their sons and daughters, as well as the absence of an application that helps lecturers in their activities. provide methods to students during their study period at Madura University. With this problem, it is necessary to design an Android-based application which is expected to help Student Guardians and Student Guardian Lecturers in monitoring and managing student development both in academics and administration at Madura University by building and designing Android-based Student Lecturer Guardian application.